A Randomized, Placebo‐Controlled Crossover Study with Dipyridamole for Restless Legs Syndrome. Issue 10 (17th June 2021) - Garcia‐Borreguero, Diego; Garcia‐Malo, Celia; Granizo, Juan José; Ferré, Sergi
ABSTRACT: Background: New pharmacological targets are needed for restless legs syndrome. Preclinical data suggest that a hypoadenosinergic state plays an important pathogenetic role. Objective: The objective of this study was to determine whether inhibitors of equilibrative nucleoside transporters, for example, dipyridamole, could provide effective symptomatic treatment. Methods: A 2‐week double‐blind, placebo‐controlled crossover study assessed the efficacy of dipyridamole (possible up‐titration to 300 mg) in untreated patients with idiopathic restless legs syndrome. Multiple suggested immobilization tests and polysomnography were performed after each treatment phase. Severity was assessed weekly using the International Restless Legs Rating Scale, Clinical Global Impression, and the Medical Outcomes Study Sleep scale. The primary end point was therapeutic response. Results: Twenty‐eight of 29 patients recruited were included. International Restless Legs Rating Scale scores improved from a mean ± standard deviation of 24.1 ± 3.1 at baseline to 11.1 ± 2.3 at the end of week 2, versus 23.7 ± 3.4 to 18.7 ± 3.2 under placebo ( P  < 0.001). Clinical Global Impression, Medical Outcomes Study Sleep, and Multiple Suggested Immobilization Test scores all improved ( P  < 0.001). The mean effective dose of dipyridamole was 217.8 ± 33.1 mg/d. Sleep variables improved. The mean periodic leg movement index at the end of treatment with dipyridamole was 8.2 ± 3.5 versus. 28.1 ± 6.7 under placebo. Side effects (dipyridamole vs placebo) included abdominal distension (18% vs. 7%), dizziness (10.7% vs 7.1%), diarrhea, and asthenia (each 7.1% vs 3.6%). Conclusions: Dipyridamole has significant therapeutic effects on both sensory and motor symptoms of restless legs syndrome and on sleep. Our findings confirm the efficacy of dipyridamole in restless legs syndrome predicted from preclinical studies and support a key role of adenosine in restless legs syndrome. © 2021 The Authors. Movement Disorders published by Wiley Periodicals LLC on behalf of International Parkinson and Movement Disorder Society